Non-hepatitis-associated mixed cryoglobulinemia with polyclonal plasma cells disease and alcoholic cirrhosis: A rare case report - Luo, Jiao; Liu, Cheng; Lv, Qing-Jian; He, Ting; Qiang, Xing; Li, Yi; Huang, Qi-Mi; He, Jia-Lin (Frontiers in Medicine, 2023)
Mixed cryoglobulinemia refers to the serum presence of a variety of cryoglobulins, which are defined as immunoglobulins that precipitate at temperatures <37°C. The most common cause of mixed cryoglobulinemia is hepatitis C virus (HCV), while other infections including hepatitis B virus (HBV) and HIV infections, lymphoproliferative and autoimmune disorders have also been associated with the disease. We reported a rare case of type II-III mixed cryoglobulinemia caused by alcoholic cirrhosis. We need to increase the awareness of and facilitate the earlier identification of mixed cryoglobulinemia in our clinical work, when encountering a patient with liver cirrhosis combined with renal impairment so that treatment can begin early, to improve the success rate of therapy and reduce the fatality rate in potentially life-saving therapy.